2012
DOI: 10.1007/s10948-012-1468-6
|View full text |Cite
|
Sign up to set email alerts
|

Sintering Temperature Dependence of Evolving Morphologies and Magnetic Properties of Ni0.5Zn0.5Fe2O4 Synthesized via Mechanical alloying

Abstract: We report on an investigation to unravel morphological and magnetic-property dependence on sintering temperature for samples of Ni 0.5 Zn 0.5 Fe 2 O 4 synthesized via mechanical alloying. The samples were sintered at various sintering temperatures from 800°C to 1000°C. The morphology of the samples was studied by means of scanning electron microscopy (SEM); hysteresis and permeability measurement were carried out using a BH hysteresisgraph system and an impedance analyzer, respectively. The morphological studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The major contribution to the magnetic losses in ferrites is due to hysteresis losses, which are based on the damping phenomena associated with spin rotations and irreversible wall displacement. In the high-frequency range, the hysteresis losses become less important because the wall displacement is mainly damped and the losses would be mos due to spin rotation [13,22,28]. Comparing Figures 7 and 8, it is observed that the off-resonance frequency region of μ″ firstly occurred and was later followed by the μ″.…”
Section: Sss Of Nickel Zinc Ferrite (Ni 06 Zn 04 Fe 2 O 4 )mentioning
confidence: 94%
See 1 more Smart Citation
“…The major contribution to the magnetic losses in ferrites is due to hysteresis losses, which are based on the damping phenomena associated with spin rotations and irreversible wall displacement. In the high-frequency range, the hysteresis losses become less important because the wall displacement is mainly damped and the losses would be mos due to spin rotation [13,22,28]. Comparing Figures 7 and 8, it is observed that the off-resonance frequency region of μ″ firstly occurred and was later followed by the μ″.…”
Section: Sss Of Nickel Zinc Ferrite (Ni 06 Zn 04 Fe 2 O 4 )mentioning
confidence: 94%
“…During grain growth, pores become fewer which act as barrier to domain wall motion due to pinning of the wall. Besides that, the increase in sintering temperature results in a decrease of the magnetic anisotropy by decreasing the internal stress and crystal anisotropy, which reduces the hindrance to the motion of domain walls [17,[21][22][23].…”
Section: Sss Of Nickel Zinc Ferrite (Ni 06 Zn 04 Fe 2 O 4 )mentioning
confidence: 99%
“…Particularly, average grain size and relative density play an important role in the magnetization process of polycrystalline ferrites: complex magnetic permeability increases with the average grain size and relative density. 2,3,8,9,11,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]39 However, very few models relating magnetic permeability to microstructure have been developed in the past, and all of them have been uniquely tested at a specific constant angular frequency. In this regard, it is worth mentioning the models proposed by Globus, 36 Rikukawa, 38 Johnson and Visser, 25 and Pankert.…”
Section: Dependence Of Complex Magnetic Permeability On Microstructurementioning
confidence: 99%
“…Several studies have reported the dependence of magnetic properties of Ni-Zn ferrites on their microstructure, chemical composition, sintering temperature, and preparation method [4][5][6]. Many researchers, including but not limited to [3,[6][7][8][9], have investigated the production of Ni-Zn ferrites via high-energy ball milling as well as the relationship between their magnetic properties, variations in their sintering temperature, composition, and certain other parameters. To the best of our knowledge, no research has been carried out to investigate the effects of a milling atmosphere on the magnetic properties of these ferrites.…”
Section: Introductionmentioning
confidence: 99%